Identification of the distinct genomic features in gastroesophageal junction adenocarcinoma and its Siewert subtypes. Issue 3 (2nd October 2020) - Geng, Qirong; Lao, Jiawen; Zuo, Xiaoyu; Chen, Shangxiang; Bei, Jin‐Xin; Xu, Dazhi
Abstract: Rates of gastroesophageal junction adenocarcinomas (GEJAs) have shown an alarming increase; however, the genetic background of GEJA and its Siewert classification have yet to be uncovered. Here, 60 paired tumor and normal DNA samples from GEJA patients were analyzed by whole‐exome sequencing. Among them, 13 were Siewert type I, 14 were type II, and 33 were type III. A predominance of C/G>T/A substitutions was discovered in GEJA, followed by C/G>A/T substitutions. Notably, Siewert type I and type II/III display distinct sets of driver genes, mutational spectrum, and recurrently disrupted pathways. Siewert type I showed similarity to esophageal adenocarcinomas (EACs) and the chromosomal instability subtype of stomach adenocarcinomas, while Siewert type II/III showed similarity to the genomic stable subtype of stomach adenocarcinoma. We also found that mutation of FBXW7, a driver gene of GEJA, was enriched in Siewert type I. Our data identify differences between GEJA and stomach/EACs at the genomic level and provide evidence for differential treatment based on Siewert classification of GEJA. © 2020 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.